The Journal of Finance - Association, American Finance (Journal of Finance, 2010)
The Journal of Finance publishes leading research across all the major fields of financial research. It is the most widely cited academic journal on finance. Each issue of the journal reaches over 8,000 academics, finance professionals, libraries, government and financial institutions around the world. Published six times a year, the journal is the official publication of The American Finance Association, the premier academic organization devoted to the study and promotion of knowledge about financial economics.